Kei te moe te tinana, kei te oho te wairua – As the body sleeps, the spirit awakens: exploring the spiritual experiences of contemporary Māori associated with sleep - Deanna Haami; Rosemary Gibson; Nicole Lindsay; Natasha Tassell-Matamua (Kōtuitui)
For Aotearoa New Zealand Māori, sleep and wairua (spirit) are closely intertwined. During sleep the wairua awakens and journeys across multiple dimensions of time and space to attain the tools and knowledge the individual needs to navigate waking life. While this function of sleep is understood within Mātauranga Māori (bodies of knowledge regarding everything within the universe) (Hikuroa 2017), it has yet to be explored within psychological sleep research. This qualitative study contributes to addressing this gap by exploring nine Māori participants’ personal experiences of wairua during sleep. A whakapapa thematic analysis identified two interconnected layers. The first layer contributed to a spiritual explanatory framework for sleep, developed to encompass participants’ beliefs regarding wairua, which were utilised to interpret their sleep experiences. The second layer describes these interpretations, comprised of three central themes: (1) Tohu/Guidance; (2) Ako/Space and time for learning; and (3) Tau/Attaining a state of stability, peace, and purpose. These findings suggest that the spiritual experience of sleep supported participants in navigating their waking lives safely, purposefully, and meaningfully, contributing to Indigenous and Māori scholarship regarding the spiritual and cultural purpose of sleep, and with important implications for clinical, social, and academic approaches to understanding and supporting sleep.